2012
DOI: 10.1103/physrevd.85.113009
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of the measurement of Higgs pair creation at a photon linear collider

Abstract: We studied the feasibility of the measurement of Higgs pair creation at a Photon Linear Collider (PLC). From the sensitivity to the anomalous self-coupling of the Higgs boson, the optimum γγ collision energy was found to be around 270 GeV for a Higgs mass of 120 GeV/c 2 . We found that large backgrounds such as γγ → W + W − , ZZ, and b bb b, can be suppressed if correct assignment of tracks to parent partons is achieved and Higgs pair events can be observed with a statistical significance of ∼ 5σ by operating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…We have also given an estimate of the statistical sensitivity (S stat ) as given in [28], with L being the Luminosity. σ and σ SM are the cross section of the Higgs boson production in the CHMs and SM, while L, η, η BG , and σ BG are the integrated luminosity, the detection efficiency for the signal, the detection efficiency for backgrounds, and the cross section of background processes, respectively.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also given an estimate of the statistical sensitivity (S stat ) as given in [28], with L being the Luminosity. σ and σ SM are the cross section of the Higgs boson production in the CHMs and SM, while L, η, η BG , and σ BG are the integrated luminosity, the detection efficiency for the signal, the detection efficiency for backgrounds, and the cross section of background processes, respectively.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For the statistical sensitivity we have used an integrated luminosity of L = 2 ab −1 . The backgrounds used in the estimation are as given in [28] and used the cut efficiencies as estimated in table V of [28]. In estimating the statistical significance we have evaluated the cross-section (for signal and backgrounds) as a function of E γγ whereas the cut efficiencies as given in [28] are taken to be constant.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an extensive study of the feasibility of the diHiggs production with a parameter set of the ILC-based photon collider was reanalysed in ref. [102], which concluded that that the channel γγ → hh → bbbb process can be observed with a statistical significance of about 5σ for the integrated luminosity corresponding to 5 years running of the photon collider. Therefore, the photon collider provide an ideal place to study the new physics effect in the di-Higgs production.…”
Section: Introductionmentioning
confidence: 99%